Utveckling av mätsystem för termisk studie av transformator - Johnsson Hjort, Marcus; Örnberg, Erik (My University, 2013)
The main limiting factor with respect to continuous power handling in electrical machines and transformers is the temperature rise in the windings. Thermal models are therefore a valuable tool in the design process to be able to predict the operational temperature at certain operating points. To be able to construct such models, an accurate measurement system is needed to obtain the temperature in several positions over the test object. This report describes the construction, calibration and evaluation of such a system. The system has eight channels where each channel is made up by of resistance thermometers, wheatstone bridges with amplification and separate data handling process. All testing are done on an ETD ferrite core with only one winding connected to a DC voltage supply. As a part of the objective of this report, the results from the measurements shall then be analysed to obtain thermal properties for the test object. Regarding accuracy, the system performs well and the temperatures registered can be trusted. Due to very similar temperature levels in windings, they can be modelled as one part. The most important thermal resistance is between the surface of the object to the ambient air. A simple model is then constructed and tested.
Keywords: Elkraftteknik; Electric power engineering